Deficiency of biodegradable plastic-degrading enzyme production in a gene-deletion mutant of phyllosphere yeast, Pseudozyma antarctica defective in mannosylerythritol lipid biosynthesis ... - Saika, Azusa; Koike, Hideaki; Yarimizu, Tohru; Watanabe, Takashi; Kitamoto, Hiroko; Morita, Tomotake (figshare, 2019)
Abstract The basidiomycetous yeast Pseudozyma antarctica (currently designated Moesziomyces antarcticus) produces extracellular enzymes and glycolipids, including mannosylerythritol lipids (MELs), which are biosurfactants. Strain GB-4(0) of this species was previously isolated from rice husks and produces biodegradable plastic-degrading enzyme (Pseudozyma antarctica esterase; PaE). In this study, we generated a MEL biosynthesis-deficient strain (∆PaEMT1) by deleting the gene PaEMT1, which is essential to MEL biosynthesis in strain GB-4(0). The resulting ∆PaEMT1 strain showed deficient PaE activity, and the corresponding signal was hardly detected in its culture supernatant through western blotting analysis using rabbit anti-PaE serum. On the other hand, the relative expression of the gene PaCLE1, encoding PaE, was identical between GB-4(0) and ∆PaEMT1 based on quantitative real-time PCR. When strain ∆PaEMT1 was grown in culture media supplemented with various surfactants, i.e., Tween20, BRIJ35 and ...